OPTIMASI SUHU PADA PROSES SEAM SEALING UNTUK MENINGKATKAN KINERJA TAHAN AIR PADA JAKET WATERPROOF - Murti, Wilda; Hanafi, Andhi Sukma; Noviana, Kamelia Yogi (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The seam sealing process is a crucial stage in the production of waterproof garments, serving to close stitch holes and prevent water penetration. However, the quality of the seam seal highly depends on process parameters such as temperature, pressure, and machine speed. This study investigates the effect of sealing temperature variation on the waterproof performance of seam seals using two different adhesive tapes. Two fabric samples were tested: Sample A (polyurethane–polyester blended tape) and Sample B (pure polyester tape). The tests were conducted following the AATCC 127:2022 standard using a Hydrostatic Pressure Tester with water at 21 ± 2°C and a pressure increase rate of 60 mbar/min; the hydrostatic head value (mmH?O) was recorded when the first three water droplets appeared on the dry side of the fabric. In addition to the supplier’s recommended temperature (480°C), sealing temperatures ranging from 230°C to 500°C were applied to determine the optimal temperature. The results showed that Sample A maintained stable waterproof performance across a wider temperature range (260–470°C), achieving the highest value of 9812.71 mmH?O at 470°C. In contrast, Sample B reached its peak value of 5710.41 mmH?O at 410°C and exhibited greater sensitivity to temperature changes. These findings indicate that the tape composition (presence of polyurethane) and the precise selection of sealing temperature are key factors in achieving optimal waterproof seam quality. Further research is recommended to optimize process parameters (temperature, pressure, and contact time) and to evaluate long-term durability for waterproof garment manufacturing applications. ABSTRAK Proses seam sealing merupakan tahap penting dalam pembuatan pakaian tahan air (waterproof jacket) yang berfungsi menutup celah jahitan agar tidak tembus air. Namun, kualitas hasil seam seal sangat bergantung pada pengaturan parameter proses seperti suhu, tekanan, dan kecepatan mesin. Penelitian ini menelaah pengaruh variasi suhu penyegelan terhadap kekedapan air sambungan jahitan (seam seal) pada dua jenis sampel kain menggunakan pita perekat tape berbeda. Dua sampel yang diuji adalah: Sampel A (tape campuran poliuretan–poliester) dan Sampel B (tape poliester murni). Pengujian dilakukan berdasarkan standar AATCC 127:2022 dengan Hydrostatic Pressure Test pada kondisi air 21 ± 2°C dan laju peningkatan tekanan 60 mbar/menit; nilai hydrostatic head (mmH?O) dicatat ketika muncul tiga tetes pertama pada sisi kering kain. Selain pengujian pada suhu rekomendasi supplier (480°C), dilakukan variasi suhu dari 230°C sampai 500°C untuk menentukan suhu optimal. Hasil menunjukkan bahwa Sampel A mempertahankan kekedapan air yang stabil pada rentang luas (260–470°C) dengan nilai tertinggi 9812,71 mmH?O pada 470°C, sedangkan Sampel B menunjukkan nilai puncak 5710,41 mmH?O pada 410°C dan performa yang lebih sensitif terhadap perubahan suhu. Temuan ini mengindikasikan bahwa komposisi tape (keberadaan poliuretan) dan penentuan suhu penyegelan yang tepat merupakan faktor kunci dalam menghasilkan seam seal yang kedap air. Rekomendasi pengembangan meliputi optimasi parameter proses (suhu, tekanan, waktu kontak) dan uji ketahanan jangka panjang untuk aplikasi manufaktur pakaian tahan air.